Strain energy density criterion as failure assessment for quasi-static uni-axial tensile load - Andrea Kusch; Simone Salamina; Daniele Crivelli; Filippo Berto (Fracture and Structural Integrity)
Strain energy density is successfully used as criterion for failure assessment of brittle and quasi-brittle material behavior. This work investigates the possibility to use this method to predict the strength of V-notched specimens made of PMMA under static uniaxial tensile load. Samples are characterized by a variability of notch root radii and notch opening angles. Notched specimens fail with a quasi-brittle behavior, albeit PMMA has a nonlinear stress strain curve at room temperature. The notch root radius has most influence on the strength of the specimen, whereas the angle is less relevant. The value of the strain energy density is computed by means of finite element analysis, the material is considered as linear elastic. Failure predictions, based on the critical value of the strain energy density in a well-defined volume surrounding the notch tip, show very good agreement (error minus 15%) with experimental data.